Belief in the immutability of attitudes both increases and decreases advocacy. [article]. - Akhtar, O.
People with an entity theory of attitudes (i.e., the belief that attitudes are relatively unchanging) are more certain of their attitudes than are people with an incremental theory (i.e., the belief that attitudes are relatively malleable), and people with greater attitude certainty are generally more willing to try to persuade others. Combined, these findings suggest that an entity theory should foster greater advocacy. Yet, people with entity theories may be less willing to advocate because they also perceive others attitudes as unchanging. Across 5 studies, we show that both of these countervailing effects occur simultaneously and cancel each other out. However, by manipulating how advocacy is framed (as standing up for one's views or exchanging one's views with others), whom people focus on (themselves or others), or which implicit theory applies to oneself versus others, each implicit theory can either increase or decrease willingness to advocate.- (from the authors)
Keywords: Wheeler, C; Advocacy; Attitude certainty; Attitudes; Implicit theories; Persuation